Bridging Languages, Shaping Identities: Teachers’ Perspectives And Practices Of Translanguaging In Indonesian EFL Classrooms - Sellya Umi Kulsum Madina; Kartika Puji Lestari; Akhmad Ramadhan Ajijaya; Siti Masrifatul Fitriyah (Jurnal Multidisiplin Indonesia, 2026)
In multilingual Indonesia, EFL classrooms consist of students with diverse linguistic backgrounds, including local languages, Indonesian, and English. This diversity presents both opportunities and challenges for inclusive teaching. Translanguaging has emerged as a pedagogical approach that strategically utilizes students' full linguistic resources to enhance comprehension, participation, and identity affirmation. The research investigated how translanguaging contributes to social inclusion and comprehension improvement and cultural identity preservation in Indonesian multilingual EFL classrooms. The research implemented a qualitative case study methodology to collect data from six EFL teachers using semi-structured interviews and a focus group discussion. Thematic analysis Braun and Clarke were used to analyze data which revealed patterns of perceptions and practices. Five primary themes appeared as follows: translanguaging to promote inclusion alongside cultural identity, perspectives of teachers regarding translanguaging, methods of translanguaging in classroom settings, obstacles for implementing translanguaging and teacher methods for adapting and using translanguaging. The research indicates that translanguaging through planned incorporation of Indonesian, local languages, and English led to greater participation, cultural affirmation, and improved access to content. Teachers used multilingual techniques which included vocabulary translation, flexible multilingual interaction, and collaborative group work. The teachers employed adaptable methods through reflective practices and situational awareness to determine when and how to employ translanguaging effectively. The research indicates that translanguaging operates as an educational approach as well as a social and cultural practice within EFL classrooms. Translanguaging implementation in Indonesian multilingual education needs enhanced teacher training together with adaptable curricula and resource development.